AS QUATRO OPERAÇÕES FUNDAMENTAIS DA ARITMÉTICA: CONHECIMENTOS PRÉVIOS DOS ALUNOS NO INÍCIO DO 1º ANO DO ENSINO MÉDIO - Schirlo, João Luiz (2014)
Mathematics is part of everyone's life both on facts of everyday life, as in the act of telling and operate on quantities, as for complex facts, as in the formulation and derivation of relations of a theory that requires the use of mathematical rigor. In this context, namely solving the four fundamental operations of arithmetic - addition, subtraction, multiplication and division - is essential for the student to learn to solve basic situations of your everyday life as well as to solve the school problem situations. Given this fact, in this research devised to the conclusion of the Professional Master's Program in Mathematics in National Network, there was a exploratory research in order to answer the following question: What prior knowledge on the four fundamental operations of arithmetic, students from two state public schools of the city of Ponta Grossa, presented at the beginning of the 1st year of high school?, aiming to probe the prior knowledge on the four fundamental operations of arithmetic. To do so, we applied an activity with addition, subtraction, multiplication and division operations in order to obtain information about the prior knowledge that the subjects - 203 students, aged between 13 and 20 years, from seven classes in the 1st year of high school, in the morning, afternoon and night - this research presented on these operations. It is noteworthy that the analysis of the data was raised a qualitative study and showed that several students had prior knowledge to develop operations that do not require regrouping carry and do not involve decimals. In particular, the multiplication operations, few students have had prior knowledge of multiplication tables, mainly from the 6 times table. And in division operations, which require prior knowledge related subtraction and multiplication, only a minority of students have presented these knowledge to solve them. Thus, knowing these data can contribute to effective learning of students and teachers' reflections about their methodological practices to be used in the classroom. For example, to fill the gap of the previous knowledge that the subjects of this research have presented, it is suggested the use of Table Value Place because this material is a feature that enhances the meaning of the decimal positional representation that can help them domain have the fundamental principle of the decimal number system, thus, understanding the function of groups and trade. Then it is understood that probe the prior knowledge that the subjects of this research presented on the four fundamental operations of arithmetic is necessary to respect the structure of a cumulative discipline such as Mathematics. Furthermore, we note that prior knowledge plays a key role in the discipline of mathematics activity because only adds to unify concepts and lines of reasoning and adapting known methods and new content results.